New Mechanisms of Action of Natural Antioxidants in Health and Disease - Angeloni, Cristina; Hrelia, Silvana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book contributes to increasing the knowledge on the mechanisms of action of natural antioxidants, evidencing their pleiotropic role in the prevention and/or counteraction of degenerative diseases, and promoting their application in the functional food and cosmetic fields.